Postgraduate students’ experience of poverty and academic success at a university of technology in South Africa - Machika, P.; Johnson, B (South African Journal of Higher Education, 2016)
Poverty within a developing context such as South Africa has been deepening, with the pressures of globalisation and neo-liberalism resulting in the widening gap between the rich and the poor. For students from a poor background an opportunity to study at a higher education institution is an opportunity to change their economic status at a personal and family level; however, it is difficult to achieve this goal when the very economic conditions they live in have an impact on their ability be academically successful. The study is concerned with poverty under which postgraduate students live, think and learn while studying and how this affects their academic success. Semi-structured individual interviews were conducted with 34 postgraduate students. The main aim of the article is to contribute to an understanding of how funding of academic students by government and higher education institutions could be utilised to enable their academic success. Keywords: Academic success, poverty, universities, understanding, funding